Assessing Air-Surface Exchange and Fate of Mercury in a Subtropical Forest Using a Novel Passive Exchange-Meter Device - Zhang, Hui; Nizzetto, Luca; Feng, Xinbin; Borgå, Katrine; Sommar, Jonas; Fu, Xuewu; Zhang, Hua; Zhang, Gan; Larssen, Thorjørn (Environmental science & technology, 2019)
A novel passive exchange meter (EM) device was developed to assess air-surface exchange and leaching of Hg in a forest floor. Flux measurements were carried out in a subtropical forest ecosystem during a full year. Over 40% of the Hg fixed in fresh forest litter was remobilized in less than 60 days in warm and humid conditions as a response to rapid turnover of labile organic matter (OM). A two-block experiment including understory and clearing showed that losses of Hg covaried with seasonal conditions and was significantly affected by forest coverage. The process controlling the bulk loss of total Hg from the litter was volatilization, which typically represented 76-96% of the loss processes (Floss). The Floss ranges were 520-1370 and 165-942 ng m-2 d-1 in the understory and clearing, respectively. On a yearly basis, deposition of airborne Hg exceeded total losses by a factor of 2.5 in the clearing and 1.5 in the understory. The vegetation litter in this subtropical forest therefore represented a net sink of atmospheric Hg. This study provided a novel approach to Hg air-soil exchange measurements and further insights on the link between Hg remobilization and OM turnover along with its environmental drivers.
Keywords: stromy; ekosystém; Forests; rtuť; látky znečišťující půdu; Ecosystem; Mercury; Soil; půda; Trees; Soil Pollutants; Environmental Monitoring; monitorování životního prostředí; lesy